Narratives of note studies of popular forms in the twentieth century - Reyes, Soledad s. (University of Santo Tomas Publishing House, 2012)
Narrative of note is a collection of critical essays written between 2006-2010. The anthology includes studies on such genres as the Tagalog novel and the komiks; on the powerful institution, Liwayway magazines;and on the dominanr critical approaches in contemporary criticism as deployed by a number of Filipino critics.